Screening for diabetes and hypertension in adult dental patients: the experience in a Nigerian dental center - Nnawuihe, Ukachi Chiwendu; Adelusi, Emmauel Adetolu; Salami, Afolake Shakirat; Adebayo, Ezekiel Taiwo; Ahaji, Lilian Ejije (Frontiers in Dental Medicine, 2024)
Objectives The aim of the present study was to examine the presentation of hypertension and diabetes mellitus in dental patients. Methods Dental patients were screened for hypertension and elevated blood sugar using a sphygmomanometer and a glucometer, respectively. Results A total of 102 men and 129 women participated in the study. In total, 69 (29.9%) and 20 (8.7%) participants reported a history of hypertension and diabetes mellitus, respectively. Adherence to taking hypertensive and diabetic medications as advised by a clinician was reported by 68.0% and 85.0% of patients with known hypertension and diabetes, respectively, of whom 29.8% had uncontrolled hypertension and 29.4% had high blood sugar in the diabetic range (>200 mg/dl). In patients with no history of these diseases, 42 (25.9%) had elevated blood pressure, while 5 (2.4%) had high blood sugar in the diabetic range. The prevalence of hypertension was 37.3% and high blood sugar in the diabetic range was 5.2% in the sample. Individuals with diabetes were 31 times more likely to have hypertension than those without diabetes (odds ratio = 31.06, 95% confidence interval 5.68–169.98, p ≤ 0.001). Conclusion Screening was helpful in the detection of undiagnosed cases and suboptimal control of both diseases in patients. Recommendations for dental practice guidelines include routine screening with mandatory screening for hypertension in patients with diabetes.